How to be Critically Open-Minded: A Psychological and Historical Analysis - Lambie, J. author. aut Link
XIII, 239 p.
Keywords: In a lively and subversive analysis, psychologist John Lambie explains how to see another person's point of view while remaining critical – in other words how to be 'critically open-minded'. Using entertaining examples from history and psychology, Lambie explores the implications of critical open-mindedness for scientific and moral progress.